REVEALED COMPARATIVE ADVANTAGE INDEX OF BRAZILIAN AVOCADO IN INTERNATIONAL TRADE - Julio, Fabíola Damiani; Bueno, Ana Flávia Garcia Moraes (Revista Interface Tecnológica, 2022)
Brazil is competitive in fruit demonstrating potential to become an exporter of fruits and the export of avocados shown as an opportunity for diversification and higher profitability of farming. The world avocado industry is very promising and Brazil has conditions to actively participate in this market. There is possibility to export the fruit "in natura ’’ and also the fruit by-products such as frozen pulp and avocado oil. The fruits that have no export patterns can be processed and exported as by-product adding value production. The advantages of producing avocado in Brazil are long period of harvest allowing the selection of the suitable times for export and availability of vast size and climate conditions. To measure the competitiveness of Brazilian avocado in the international market we calculated the index of revealed comparative advantage from 2000 to 2011. The results found ranged from 0.11 to 0.22 indicating the absence of revealed comparative advantage. However, Brazilian exports have increased in the period analyzed showing that Brazil seems to be closer to international opportunities.